High-performance all-solid-state battery pole piece and preparation method thereof
By adopting composite coating and multi-stage particle size matching technology in all-solid-state battery pole sheets, the problem of impedance changes in the electrode sheet during charging and discharging is solved, and the preparation of high-performance all-solid-state battery pole sheets is realized, which improves the battery overall performance.
Patent Information
- Application Number
- CN202411561206.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-04
- Publication Date
- 2025-02-18
AI Technical Summary
The existing all-solid-state battery pole plates are prone to change impedance during charging and discharging, affecting battery performance, and the preparation technology has the problem that high-performance pole plates are difficult to achieve.
High-performance all-solid battery electrodes composed of current collector and active substance coating, the coating contains uniformly mixed composite active substance particles, composite solid electrolyte particles, conductive agents and adhesives, and the active substances and solid electrolytes are carried out by performing the The composite coating process reduces the contact impedance between particles and increases the compactness of the electrode sheet through multi-stage particle size matching.
It effectively reduces the impedance changes of the electrode plate during charging and discharging, and improves the performance of all-solid-state batteries, including improving energy density and cycle life.
Smart Images

Figure CN119480887A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of all-solid-state batteries, and in particular to an all-solid-state battery pole piece and a preparation method thereof. Background Art
[0002] Traditional liquid lithium-ion batteries have inherent limitations in safety and energy density, which has prompted scientists to explore new battery technologies, among which all-solid-state batteries have attracted much attention due to their excellent safety and potential high energy density. All-solid-state batteries use solid electrolytes instead of traditional liquid electrolytes, which greatly improves the safety and stability of the battery. In addition, all-solid-state batteries also have the advantages of high energy density, long cycle life and wide temperature adaptability, and are considered to be an important development direction for the next generation of battery technology.
[0003] Although all-solid-state batteries have many advantages, their commercialization process still faces many challenges, one of which is the preparation technology of high-performance all-solid-state battery pole pieces. The pole piece is the core component of the battery, and its performance directly affects the overall performance of the battery. In the prior art, all-solid-state batteries directly use uncoated active material particles and solid electrolyte particles, and the contact impedance between particles is large; and the active material particles and solid electrolyte particles of a single particle size are used, and the internal gap of the prepared pole piece is large and the compactness is low. The pole piece is prone to impedance changes during the charge and discharge process, which affects the performance of the all-solid-state battery. Summary of the invention
[0004] The purpose of the present invention is to provide a high-performance all-solid-state battery electrode to solve the above technical problems;
[0005] The present invention also aims to provide a method for preparing a high-performance all-solid-state battery electrode to solve the above technical problems.
[0006] The technical problem solved by the present invention can be achieved by adopting the following technical solutions:
[0007] A high-performance all-solid-state battery pole piece comprises a current collector and an active material coating arranged on the surface of the current collector, wherein the active material coating comprises uniformly mixed composite active material particles, composite solid electrolyte particles, a conductive agent and an adhesive; the composite active material particles comprise first-type composite active material particles whose surfaces are coated with third-type composite solid electrolyte particles and second-type composite active material particles whose surfaces are coated with the third-type composite solid electrolyte particles; the composite solid electrolyte particles comprise first-type composite solid electrolyte particles whose surfaces are coated with the third-type composite solid electrolyte particles, second-type composite solid electrolyte particles whose surfaces are coated with the third-type composite solid electrolyte particles and the third-type composite solid electrolyte particles.
[0008] Preferably, the current collector is a positive electrode current collector or a negative electrode current collector, and the positive electrode current collector is one of aluminum foil, microporous aluminum foil, corroded aluminum foil, composite aluminum foil, copper foil, microporous copper foil, corroded copper foil, composite copper foil, steel foil, corroded steel foil and microporous steel foil; the negative electrode current collector is one of aluminum foil, microporous aluminum foil, corroded aluminum foil, composite aluminum foil, copper foil, microporous copper foil, corroded copper foil, composite copper foil, steel foil, corroded steel foil and microporous steel foil;
[0009] The thickness of the positive electrode current collector is 4 um to 20 um, and the thickness of the negative electrode current collector is 4 um to 15 um.
[0010] Preferably, the first type of composite active material particles include first type active material particles and third type composite solid electrolyte particles coated on the surface of the first type active material particles, and the coating thickness is 30nm to 100nm;
[0011] The ratio of the first type of active material particles to the third type of composite solid electrolyte particles is (90:10) to (95:5);
[0012] The particle size D50 parameter of the first type of composite active material particles is 3.0 um to 4.0 um, and the particle size D50 parameter of the first type of active material particles is 2.5 um to 3.5 um.
[0013] Preferably, the second type of composite active material particles include the second type of active material particles and the third type of composite solid electrolyte particles coated on the surface of the second type of active material particles, and the coating thickness is 10nm to 50nm;
[0014] The ratio of the second type of active material particles to the third type of composite solid electrolyte particles is (80:20) to (90:10);
[0015] The particle size D50 parameter of the second type of composite active material particles is 1.5um to 2.5um, and the particle size D50 parameter of the second type of active material particles is 0.8um to 1.8um.
[0016] Preferably, the ratio of the first type of composite active substance particles to the second type of composite active substance particles contained in the composite active substance particles is (55:45) to (80:20);
[0017] The weight ratio of the first type of composite solid electrolyte particles, the second type of composite solid electrolyte particles and the third type of composite solid electrolyte particles included in the composite solid electrolyte particles is (50:35:15) to (70:25:5).
[0018] Preferably, the first type of composite solid electrolyte particles include first type of inorganic solid electrolyte particles and the third type of composite solid electrolyte particles coated on the first type of inorganic solid electrolyte particles, and the coating thickness is 10nm to 50nm;
[0019] The ratio of the first type of inorganic solid electrolyte particles to the third type of composite solid electrolyte particles is (75:25) to (90:10);
[0020] The particle size D50 parameter of the first type of composite solid electrolyte particles is 1.2um to 2.0um, and the particle size D50 parameter of the first type of inorganic solid electrolyte particles is 0.8um to 1.5um;
[0021] The first type of inorganic solid electrolyte particles is an inorganic oxide solid electrolyte or a sulfide solid electrolyte or a mixture of an inorganic oxide solid electrolyte and a sulfide solid electrolyte.
[0022] Preferably, the second type of composite solid electrolyte particles include the second type of inorganic solid electrolyte particles and the third type of composite solid electrolyte particles coated on the surface of the second type of inorganic solid electrolyte particles, and the coating thickness is 5nm to 30nm;
[0023] The ratio of the second type of inorganic solid electrolyte particles to the third type of composite solid electrolyte particles is (60:40) to (80:20);
[0024] The particle size D50 parameter of the second type of composite solid electrolyte particles is 0.4um to 0.8um, and the particle size D50 parameter of the second type of inorganic solid electrolyte particles is 0.2um to 0.6um;
[0025] The second type of inorganic solid electrolyte particles is an inorganic oxide solid electrolyte or a sulfide solid electrolyte or a mixture of an inorganic oxide solid electrolyte and a sulfide solid electrolyte.
[0026] Preferably, the active material coating is a positive electrode active material coating or a negative electrode active material coating, the thickness of the positive electrode active material coating is 10um to 300um, and the thickness of the negative electrode active material coating is 10um to 300um;
[0027] The composite active material particles are positive electrode composite active material particles or negative electrode composite active material particles, and the conductive agent is a positive electrode conductive agent or a negative electrode conductive agent; the positive electrode active material coating includes the positive electrode composite active material particles, the positive electrode conductive agent, the composite solid electrolyte particles and the adhesive; the negative electrode active material coating includes the negative electrode composite active material particles, the negative electrode conductive agent, the composite solid electrolyte particles and the adhesive.
[0028] Preferably, the positive electrode active material of the positive electrode composite active material particles includes LiCoO2, LiNi x Co y Mn z O 2 (x+y+z=1), LiNi x Co y Al z O 2 (x+y+z=1),NaNi x Fe y Mn z Cu w O 2 (x+y+z+w=1), Na x M1[M2(CN) 6 ](0<x<6);
[0029] The positive electrode active material of the negative electrode composite active material particles includes graphite, Si, Li 4 Ti 5 O 12 , at least one of hard carbon and soft carbon;
[0030] The positive electrode conductive agent includes at least one of electric carbon black, carbon nanotubes, graphene and carbon fibers, and the negative electrode conductive agent includes at least one of electric carbon black, carbon nanotubes, graphene and carbon fibers.
[0031] Preferably, the third type of composite solid electrolyte particles is a mixture of an organic polymer solid electrolyte and an inorganic electrolyte salt, with a weight ratio of (85:15) to (95:5); wherein the organic polymer solid electrolyte is at least one of polyethylene oxide, polymethyl methacrylate, polyvinylidene fluoride-copolymer, and hydrogenated nitrile rubber, and the inorganic electrolyte salt is at least one of lithium hexafluorophosphate, sodium hexafluorophosphate, lithium tetrafluoroborate, sodium tetrafluoroborate, sodium bis(trifluoromethylsulfonyl)imide, lithium bis(trifluoromethylsulfonyl)imide, lithium difluoroborate, and sodium difluoroborate;
[0032] The particle size D50 parameter of the third type of composite solid electrolyte particles is 0.1um to 0.3um.
[0033] A method for preparing a high-performance all-solid-state battery pole piece, used for preparing the all-solid-state battery pole piece, comprising:
[0034] Step S1, fully melting the organic polymer solid electrolyte under a certain temperature and stirring conditions, adding an inorganic electrolyte salt, and fully mixing them under a certain temperature and stirring conditions to form a molten slurry;
[0035] Step S2, spraying and cooling the molten slurry to obtain the third type of composite solid electrolyte particles; adding the first type of active material particles to the molten slurry and mixing them thoroughly, spraying and cooling to obtain the first type of composite active material particles; adding the second type of active material particles to the molten slurry and mixing them thoroughly, spraying and cooling to obtain the second type of composite active material particles; adding the first type of inorganic solid electrolyte particles to the molten slurry and mixing them thoroughly, spraying and cooling to obtain the first type of composite solid electrolyte particles; adding the second type of inorganic solid electrolyte particles to the molten slurry and mixing them thoroughly, spraying and cooling to obtain the second type of composite solid electrolyte particles;
[0036] Step S3, uniformly mixing the composite active material particles, the composite solid electrolyte particles, the conductive agent, and the adhesive according to a certain ratio, processing the adhesive into adhesive fibers, and making the composite active material particles, the composite solid electrolyte particles, and the conductive agent coated with the adhesive fibers into the active material coating;
[0037] Step S4, pressing the current collector and the active material coating by multi-roll hot pressing under certain temperature and pressure conditions to obtain the all-solid-state battery electrode.
[0038] Preferably, in step S3, the adhesive comprises at least one of polyvinylidene fluoride, polytetrafluoroethylene, polyvinyl alcohol, and polyacrylic acid, the thickness of the active material coating is 50 um to 300 um, and the ratio of the composite active material particles, the composite solid electrolyte particles, the conductive agent, and the adhesive is (80:15:2:3) to (90:8:1:1);
[0039] In step S4, the temperature of the first section of the multi-roller hot pressing is 45°C to 60°C, the temperature of the second section is 80°C to 100°C, the temperature of the third section is 15°C to 30°C, the pressure of the first section is 5MPa to 20MPa, the pressure of the second section is 30MPa to 60MPa, and the pressure of the third section is 70MPa to 100MPa.
[0040] Beneficial effects of the present invention: Due to the adoption of the above technical scheme, the present invention reduces the contact impedance between particles by composite coating treatment of active materials and solid electrolytes, and simultaneously adopts a multi-level particle size matching method for composite active material particles and composite solid electrolyte particles to increase the compactness of the electrode, reduce the impedance change of the electrode during the charging and discharging process, thereby improving the performance of the all-solid-state battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0041] Figure 1 Schematic diagram of the structure of an all-solid-state battery electrode in an embodiment of the present invention;
[0042] Figure 2 Schematic diagram of the first type of composite active material particles in an embodiment of the present invention;
[0043] Figure 3 Schematic diagram of the second type of composite active material particles in an embodiment of the present invention;
[0044] Figure 4 Schematic diagram of the first type of composite solid electrolyte particles in an embodiment of the present invention;
[0045] Figure 5 Schematic diagram of the second type of composite solid electrolyte particles in an embodiment of the present invention;
[0046] Figure 6 Schematic diagram of the third type of composite solid electrolyte particles in an embodiment of the present invention;
[0047] Figure 7 Schematic diagram of the steps of the method for preparing a high-performance all-solid-state battery electrode in an embodiment of the present invention.
[0048] In the attached drawings: 100, all-solid-state battery pole piece; 110, active material coating; 111, first type of composite active material particles; 1111, first type of active material particles; 112, second type of composite active material particles; 1121, second type of active material particles; 113, first type of composite solid electrolyte particles; 1131, first type of inorganic solid electrolyte particles; 114, second type of composite solid electrolyte particles; 1141, second type of inorganic solid electrolyte particles; 115, third type of composite solid electrolyte particles; 120, current collector. DETAILED DESCRIPTION
[0049] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0050] It should be noted that, in the absence of conflict, the embodiments of the present invention and the features in the embodiments may be combined with each other.
[0051] The present invention will be further described below in conjunction with the accompanying drawings and specific embodiments, but they are not intended to limit the present invention.
[0052] A high-performance all-solid-state battery electrode, such as Figures 1 to 6As shown, it includes a current collector 120 and an active material coating 110 arranged on the surface of the current collector 120, the active material coating 110 includes uniformly mixed composite active material particles, composite solid electrolyte particles, a conductive agent and an adhesive; the composite active material particles include first-type composite active material particles 111 whose surfaces are coated with third-type composite solid electrolyte particles 115 and second-type composite active material particles 112 whose surfaces are coated with third-type composite solid electrolyte particles 115; the composite solid electrolyte particles include first-type composite solid electrolyte particles 113 whose surfaces are coated with third-type composite solid electrolyte particles 115, second-type composite solid electrolyte particles 114 and third-type composite solid electrolyte particles 115 whose surfaces are coated with third-type composite solid electrolyte particles 115.
[0053] Specifically, the present invention provides a high-performance all-solid-state battery pole piece 100, which includes a current collector 120 and an active material coating 110; the active material coating 110 includes composite active material particles, a conductive agent, composite solid electrolyte particles and an adhesive; the composite active material particles include first-type composite active material particles 111 whose surfaces are coated with third-type composite solid electrolyte particles 115 and second-type composite active material particles 112 whose surfaces are coated with third-type composite solid electrolyte particles 115; the composite solid electrolyte particles include first-type composite solid electrolyte particles 113 whose surfaces are coated with third-type composite solid electrolyte particles 115 and second-type composite solid electrolyte particles 114 whose surfaces are coated with third-type composite solid electrolyte particles 115; the present invention reduces the contact impedance between particles by composite coating treatment of active materials and solid electrolytes, and increases the compact density of the pole piece by mixing composite active material particles and composite solid electrolyte particles of different particle sizes, and reduces the impedance change of the pole piece during charging and discharging, thereby improving the performance of the all-solid-state battery.
[0054] In a preferred embodiment, the current collector 120 is a positive electrode current collector or a negative electrode current collector, and the positive electrode current collector is one of aluminum foil, microporous aluminum foil, corroded aluminum foil, composite aluminum foil, copper foil, microporous copper foil, corroded copper foil, composite copper foil, steel foil, corroded steel foil and microporous steel foil; the negative electrode current collector is one of aluminum foil, microporous aluminum foil, corroded aluminum foil, composite aluminum foil, copper foil, microporous copper foil, corroded copper foil, composite copper foil, steel foil, corroded steel foil and microporous steel foil;
[0055] The thickness of the positive electrode current collector is 4um to 20um, preferably 5um to 12um; the thickness of the negative electrode current collector is 4um to 15um, preferably 4um to 10um.
[0056] In a preferred embodiment, Figure 2As shown, the first type of composite active material particles 111 include first type active material particles 1111 and third type composite solid electrolyte particles 115 coated on the surface of the first type active material particles 1111, and the coating thickness is 30nm to 100nm;
[0057] The ratio of the first type active material particles 1111 to the third type composite solid electrolyte particles 115 is (90:10) to (95:5);
[0058] The particle size D50 parameter of the first type composite active material particles 111 is 3.0 um to 4.0 um, and the particle size D50 parameter of the first type active material particles 1111 is 2.5 um to 3.5 um.
[0059] In a preferred embodiment, Figure 3 As shown, the second type of composite active material particles 112 include second type active material particles 1121 and third type composite solid electrolyte particles 115 coated on the surface of the second type active material particles 1121, and the coating thickness is 10nm to 50nm;
[0060] The ratio of the second type active material particles 1121 to the third type composite solid electrolyte particles 115 is (80:20) to (90:10);
[0061] The particle size D50 parameter of the second type composite active material particles 112 is 1.5 um to 2.5 um, and the particle size D50 parameter of the second type active material particles 1121 is 0.8 um to 1.8 um.
[0062] In a preferred embodiment, the ratio of the first type of composite active material particles 111 to the second type of composite active material particles 112 included in the composite active material particles is (55:45) to (80:20);
[0063] The weight ratio of the first type of composite solid electrolyte particles 113 , the second type of composite solid electrolyte particles 114 and the third type of composite solid electrolyte particles 115 included in the composite solid electrolyte particles is (50:35:15) to (70:25:5).
[0064] In a preferred embodiment, Figure 4 As shown, the first type of composite solid electrolyte particles 113 include first type of inorganic solid electrolyte particles 1131 and third type of composite solid electrolyte particles 115 coated on the first type of inorganic solid electrolyte particles 1131, and the coating thickness is 10nm to 50nm;
[0065] The ratio of the first type of inorganic solid electrolyte particles 1131 to the third type of composite solid electrolyte particles 115 is (75:25) to (90:10);
[0066] The particle size D50 parameter of the first type of composite solid electrolyte particles 113 is 1.2um to 2.0um, and the particle size D50 parameter of the first type of inorganic solid electrolyte particles 1131 is 0.8um to 1.5um;
[0067] The first type of inorganic solid electrolyte particles 1131 are inorganic oxide solid electrolytes or sulfide solid electrolytes or a mixture of inorganic oxide solid electrolytes and sulfide solid electrolytes.
[0068] Specifically, the composite solid electrolyte particles include positive composite solid electrolyte particles and negative composite solid electrolyte particles; the positive composite solid electrolyte particles and the negative composite solid electrolyte particles are the same or different, and are independently composed of first type composite solid electrolyte particles 113, second type composite solid electrolyte particles 114 and third type composite solid electrolyte particles 115;
[0069] In a preferred embodiment, Figure 5 As shown, the second type of composite solid electrolyte particles 114 include second type of inorganic solid electrolyte particles 1141 and third type of composite solid electrolyte particles 115 coated on the surface of the second type of inorganic solid electrolyte particles 1141, and the coating thickness is 5nm to 30nm;
[0070] The ratio of the second type of inorganic solid electrolyte particles 1141 to the third type of composite solid electrolyte particles 115 is (60:40) to (80:20);
[0071] The particle size D50 parameter of the second type of composite solid electrolyte particles 114 is 0.4um to 0.8um, and the particle size D50 parameter of the second type of inorganic solid electrolyte particles 1141 is 0.2um to 0.6um;
[0072] The second type of inorganic solid electrolyte particles 1141 are inorganic oxide solid electrolytes or sulfide solid electrolytes or a mixture of inorganic oxide solid electrolytes and sulfide solid electrolytes.
[0073] The inorganic solid electrolyte particles used in the first type of inorganic solid electrolyte particles 1131 and the second type of inorganic solid electrolyte particles 1141 are inorganic oxide solid electrolytes or sulfide solid electrolytes or a mixture of the two electrolytes. Preferably, the inorganic solid electrolyte particles are Li 7 La 3 Zr 2 O 12 , Li 1+x AlxTi 2-x (PO 4 ) 3 、LiTaO 3 、LiNbO 3、Na 3 Zr 2 Si 2 PO 12 , Li 2 SP 2 S 5 , Li 2 SP 2 S 5 -LiCl, Li 2 SP 2 S 5 -H 2 S. Li 2 SP 2 S 5 -H 2 S-LiCl, Li 2 S-GeS 2 -Ga 2 S 3 , Li 2 S-GeS 2 -P 2 S 5 , Li 2 S-GeS 2 -Sb 2 S 5 、Na 3 PS 4 、Na 3 Sb 4 、Na 2 SP 2 S 5 、Na 11 Sn 2 PS 12 At least one of .
[0074] Specifically, the present invention reduces the contact impedance between particles by performing a composite coating treatment on the active material and the solid electrolyte, and increases the compactness of the electrode by mixing composite active material particles and composite solid electrolyte particles of different particle sizes, while simultaneously adopting a multi-level particle size matching method for the composite active material particles and the composite solid electrolyte particles, thereby reducing the impedance change of the electrode during the charge and discharge process, thereby improving the performance of the all-solid-state battery.
[0075] In a preferred embodiment, the active material coating 110 is a positive electrode active material coating or a negative electrode active material coating, the thickness of the positive electrode active material coating is 10um to 300um, and the thickness of the negative electrode active material coating is 10um to 300um;
[0076] The composite active material particles are positive electrode composite active material particles or negative electrode composite active material particles, and the conductive agent is a positive electrode conductive agent or a negative electrode conductive agent; the positive electrode active material coating includes positive electrode composite active material particles, a positive electrode conductive agent, composite solid electrolyte particles and a binder; the negative electrode active material coating includes negative electrode composite active material particles, a negative electrode conductive agent, composite solid electrolyte particles and a binder.
[0077] Specifically, the active material coating 110 is a positive electrode active material coating or a negative electrode active material coating; the thickness of the positive electrode active material coating and the negative electrode active material coating may be the same or different, and each is independently 10um to 300um, preferably 100um to 200um.
[0078] In a preferred embodiment, the positive electrode active material of the positive electrode composite active material particles includes at least one of LiCoO2, LiNixCoyMnzO2 (x+y+z=1), LiNixCoyAlzO2 (x+y+z=1), NaNixFeyMnzCuwO2 (x+y+z+w=1), and NaxM1[M2(CN)6] (0<x<6);
[0079] The positive electrode active material of the negative electrode composite active material particles includes graphite, Si, Li 4 Ti 5 O 12 , at least one of hard carbon and soft carbon;
[0080] The positive electrode conductive agent includes at least one of electric carbon black, carbon nanotubes, graphene and carbon fibers, and the negative electrode conductive agent includes at least one of electric carbon black, carbon nanotubes, graphene and carbon fibers.
[0081] Specifically, the composite active material particles include positive electrode composite active material particles and negative electrode composite active material particles, the positive electrode composite active material particles include first-type positive electrode composite active material particles and second-type positive electrode composite active material particles, the first-type positive electrode composite active material particles include first-type positive electrode active material particles, the first-type positive electrode active material particles are made of positive electrode active materials, the second-type positive electrode composite active material particles include second-type positive electrode active material particles, the second-type positive electrode active material particles are made of positive electrode active materials;
[0082] The negative electrode composite active material particles include first-type negative electrode composite active material particles and second-type negative electrode composite active material particles. The first-type negative electrode composite active material particles contain first-type negative electrode active material particles, and the first-type negative electrode active material particles are made of negative electrode active materials. The second-type negative electrode composite active material particles contain second-type negative electrode active material particles, and the second-type negative electrode active material particles are made of negative electrode active materials.
[0083] In a preferred embodiment, Figure 6 As shown, the third type of composite solid electrolyte particles 115 are a mixture of an organic polymer solid electrolyte and an inorganic electrolyte salt, with a weight ratio of (85:15) to (95:5); Figure 6 In the embodiment, the yellow outer shell is an organic polymer solid electrolyte, and the inner blue part is an inorganic electrolyte salt; wherein the organic polymer solid electrolyte is at least one of polyethylene oxide (PEO), polymethyl methacrylate (PMMA), polyvinylidene fluoride-copolymer (PVDF-HFP), and hydrogenated nitrile rubber (HNBR), and the inorganic electrolyte salt is at least one of lithium hexafluorophosphate (LiPF6), sodium hexafluorophosphate (NaPF6), lithium tetrafluoroborate (LiBF4), sodium tetrafluoroborate (NaBF4), sodium bis(trifluoromethylsulfonyl)imide (NaTFSI), lithium bis(trifluoromethylsulfonyl)imide (LiTFSI), lithium difluoroborate (LiDFOB), and sodium difluoroborate (NaDFOB);
[0084] The particle size D50 parameter of the third type of composite solid electrolyte particles 115 is 0.1 um to 0.3 um.
[0085] A method for preparing a high-performance all-solid-state battery electrode sheet, used to prepare an all-solid-state battery electrode sheet 100 in any embodiment, such as Figure 7 As shown, including,
[0086] Step S1, fully melting the organic polymer solid electrolyte under a certain temperature and stirring conditions, adding an inorganic electrolyte salt, and fully mixing them under a certain temperature and stirring conditions to form a molten slurry;
[0087] Step S2, spraying and cooling the molten slurry to obtain the third type of composite solid electrolyte particles 115; adding the first type of active material particles 1111 to the molten slurry and mixing them thoroughly, spraying and cooling to obtain the first type of composite active material particles 111; adding the second type of active material particles 1121 to the molten slurry and mixing them thoroughly, spraying and cooling to obtain the second type of composite active material particles 112; adding the first type of inorganic solid electrolyte particles 1131 to the molten slurry and mixing them thoroughly, spraying and cooling to obtain the first type of composite solid electrolyte particles 113; adding the second type of inorganic solid electrolyte particles 1141 to the molten slurry and mixing them thoroughly, spraying and cooling to obtain the second type of composite solid electrolyte particles 114;
[0088] Step S3, mixing the composite active material particles, composite solid electrolyte particles, conductive agent, and adhesive agent uniformly according to a certain ratio, processing the adhesive agent into adhesive fiber, and making the composite active material particles, composite solid electrolyte particles, and conductive agent coated with the adhesive fiber into an active material coating 110;
[0089] Step S4, pressing the current collector 120 and the active material coating 110 by multi-roll hot pressing under certain temperature and pressure conditions to obtain the all-solid-state battery electrode 100.
[0090] In a preferred embodiment, in step S3, the adhesive includes at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), polyvinyl alcohol (PVA), and polyacrylic acid (PAA), the thickness of the active material coating 110 is 50um to 300um, and the ratio of the composite active material particles, the composite solid electrolyte particles, the conductive agent, and the adhesive is (80:15:2:3) to (90:8:1:1);
[0091] In step S4, the temperature of the first section of the multi-roller hot pressing is 45°C to 60°C, the temperature of the second section is 80°C to 100°C, the temperature of the third section is 15°C to 30°C, the pressure of the first section is 5MPa to 20MPa, the pressure of the second section is 30MPa to 60MPa, and the pressure of the third section is 70MPa to 100MPa.
[0092] Specifically, another aspect of the present invention provides a method for preparing a high-performance all-solid-state battery electrode, comprising:
[0093] Step 1, preparing the third type of composite solid electrolyte particles 115,
[0094] Adding an organic polymer solid electrolyte to a high-temperature vacuum mixer and fully melting it under certain temperature and stirring conditions; adding an inorganic electrolyte salt and fully mixing it under certain temperature and stirring conditions to form a molten slurry; using a high-pressure spray device to spray and cool the molten slurry to form the third type of composite solid electrolyte particles 115;
[0095] Step 2, preparing the first type of composite solid electrolyte particles 113,
[0096] Add an organic polymer solid electrolyte to a high-temperature vacuum mixer and fully melt it under certain temperature and stirring conditions; add an inorganic electrolyte salt and fully mix it under certain temperature and stirring conditions to form a molten slurry, then add the first type of active material particles 1111 and fully mix them; use a high-pressure spray device to spray and cool the molten slurry to form the first type of composite active material particles 111;
[0097] Step 3, preparing the second type of composite active material particles 112:
[0098] Add an organic polymer solid electrolyte to a high-temperature vacuum mixer and fully melt it under certain temperature and stirring conditions; add an inorganic electrolyte salt and fully mix it under certain temperature and stirring conditions to form a molten slurry, then add the second type of active material particles 1121 and fully mix them; use a high-pressure spray device to spray and cool the molten slurry to form the second type of composite active material particles 112;
[0099] Step 4, preparing the first type of composite solid electrolyte particles 113:
[0100] Add an organic polymer solid electrolyte to a high-temperature vacuum mixer and fully melt it under a certain temperature and stirring condition; add an inorganic electrolyte salt and fully mix it under a certain temperature and stirring condition to form a molten slurry, then add the first type of inorganic solid electrolyte particles 1131 and fully mix them; use a high-pressure spray device to spray and cool the molten slurry to form the first type of composite solid electrolyte particles 113;
[0101] Step 5, preparing the second type of composite solid electrolyte particles 114:
[0102] Add an organic polymer solid electrolyte to a high-temperature vacuum mixer and fully melt it under certain temperature and stirring conditions; add an inorganic electrolyte salt and fully mix it under certain temperature and stirring conditions to form a molten slurry, then add the second type of inorganic solid electrolyte particles 1141 and fully mix them; use a high-pressure spray device to spray and cool the molten slurry to form the second type of composite solid electrolyte particles 114;
[0103] Step 6: preparing an active material coating 110,
[0104] The composite active material particles, composite solid electrolyte particles, conductive agent, and adhesive are uniformly mixed according to a certain ratio, and then the adhesive is fiberized and granulated so that the adhesive fibers fully contact and cover the composite active material particles and the composite solid electrolyte particles; the composite active material particles, composite solid electrolyte particles, and conductive agent covering the adhesive fibers are formed into an active material coating 110 by a press film forming device;
[0105] Specifically, the adhesive includes at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), polyvinyl alcohol (PVA), and polyacrylic acid (PAA);
[0106] The thickness of the active material coating 110 is 50um to 300um;
[0107] The ratio of the composite active material particles, the composite solid electrolyte particles, the conductive agent, and the adhesive in the active material coating 110 is (80:15:2:3) to (90:8:1:1);
[0108] Step 7: preparing a low-porosity, high-performance all-solid-state battery electrode 100.
[0109] The current collector 120 and the active material coating 110 are pressed into a low-porosity, high-performance all-solid-state battery pole piece 100 under certain temperature and pressure conditions using a multi-roll hot pressing device;
[0110] The temperature of the first section of the multi-roll hot pressing equipment is 45℃~60℃, the temperature of the second section is 80℃~100℃, and the temperature of the third section is 15℃~30℃;
[0111] The first-stage pressure of the multi-roll hot pressing equipment is 5MPa-20MPa, the second-stage pressure is 30MPa-60MPa, and the third-stage pressure is 70MPa-100MPa.
[0112] The present invention reduces the contact impedance between particles by performing composite coating treatment on the active material and the solid electrolyte, increases the compactness of the pole piece by mixing composite active material particles and composite solid electrolyte particles of different particle sizes, and simultaneously adopts a multi-level particle size matching method for the composite active material particles and the composite solid electrolyte particles, thereby reducing the impedance change of the pole piece during the charge and discharge process, thereby improving the performance of the all-solid-state battery.
[0113] Embodiment 1:
[0114] Step 1, preparing the third type of composite solid electrolyte particles 115,
[0115] Add an organic polymer solid electrolyte to a high-temperature vacuum mixer, and stir for 60 minutes at 80±5°C and 25Hz to fully melt it; add an inorganic electrolyte salt, and stir for 30 minutes at 80±5°C and 15Hz to fully mix it into a molten slurry; use a high-pressure spray device to spray the molten slurry and cool it to form the third type of composite solid electrolyte particles 115;
[0116] The organic polymer solid electrolyte is: PEO;
[0117] Inorganic electrolyte salt is: LiBF4;
[0118] The third type of composite solid electrolyte particles 115: D50: 0.15±0.05um;
[0119] The weight ratio of the third type of composite solid electrolyte particles 115 to the inorganic electrolyte salt is 85:15;
[0120] Step 2, preparing the first type of composite active material particles 111,
[0121] Add an organic polymer solid electrolyte to a high-temperature vacuum mixer, and stir for 60 minutes at 80±5°C and 25Hz to fully melt it; add an inorganic electrolyte salt, and stir for 30 minutes at 80±5°C and 15Hz to fully mix it into a molten slurry; then add the first type of active material particles 1111 and fully mix them; use a high-pressure spray device to spray the molten slurry and cool it to form the first type of composite active material particles 111;
[0122] The organic polymer solid electrolyte is PEO;
[0123] The inorganic electrolyte salt is LiBF4;
[0124] The first type of active material particles 1111 lithium nickel cobalt manganese oxide;
[0125] The particle size D50 parameter of lithium nickel cobalt manganese oxide particles is 2.8±0.2um;
[0126] The particle size D50 parameter of the first type of composite active material particles 111 is 3.2±0.15um;
[0127] The surface coating thickness of the third type of composite solid electrolyte is 50-70nm;
[0128] The ratio of lithium nickel cobalt manganese oxide to the third type of composite solid electrolyte particles 115 is 90:10;
[0129] Step 3, preparing the second type of composite active material particles 112,
[0130] Add an organic polymer solid electrolyte to a high-temperature vacuum mixer, stir for 60 minutes at 80±5°C and 25Hz to fully melt it; add an inorganic electrolyte salt, stir for 30 minutes at 80±5°C and 15Hz to fully mix it into a molten slurry; then add the second type of active material particles 1121 and fully mix them; use a high-pressure spray device to spray the molten slurry and cool it to form the first type of composite active material particles 111;
[0131] The organic polymer solid electrolyte is PEO;
[0132] The inorganic electrolyte salt is LiBF4;
[0133] The second type of active material particles 1121 are lithium nickel cobalt manganese oxide;
[0134] The particle size D50 parameter of lithium nickel cobalt manganese oxide particles is 1.4±0.2um;
[0135] The particle size D50 parameter of the second type of composite active material particles 112 is 1.8±0.15um;
[0136] The surface coating thickness of the third type of composite solid electrolyte is 10um to 30nm;
[0137] The ratio of lithium nickel cobalt manganese oxide to the third type of composite solid electrolyte particles 115 is 80:20;
[0138] Step 4, preparing the first type of composite solid electrolyte particles 113:
[0139] Add an organic polymer solid electrolyte to a high-temperature vacuum mixer, stir for 60 minutes at 80±5°C and 25Hz to fully melt it; add an inorganic electrolyte salt, stir for 30 minutes at 80±5°C and 15Hz to fully mix it into a molten slurry; then add the first type of inorganic solid electrolyte particles 1131 and fully mix them; use a high-pressure spray device to spray the molten slurry and cool it to form the first type of composite solid electrolyte particles 113;
[0140] The organic polymer solid electrolyte is PEO;
[0141] The inorganic electrolyte salt is LiBF4;
[0142] The first type of solid electrolyte particles is Li2S-P2S5-LiCl;
[0143] The particle size D50 parameter of Li2S-P2S5-LiCl particles is 1.0±0.2um;
[0144] The particle size D50 parameter of the first type of composite solid electrolyte particles 113 is 1.4±0.15um;
[0145] The surface coating thickness of the third type of composite solid electrolyte is 10um to 30nm;
[0146] The ratio of Li2S-P2S5-LiCl to the third type of composite solid electrolyte particles 115 is 75:25;
[0147] Step 5, preparing the second type of composite solid electrolyte particles 114:
[0148] Add an organic polymer solid electrolyte to a high-temperature vacuum mixer, stir for 60 minutes at 80±5°C and 25Hz to fully melt it; add an inorganic electrolyte salt, stir for 30 minutes at 80±5°C and 15Hz to fully mix it into a molten slurry; then add the second type of inorganic solid electrolyte particles 1141 and mix them fully; use a high-pressure spray device to spray the molten slurry and cool it to form the second type of composite solid electrolyte particles 114;
[0149] The organic polymer solid electrolyte is PEO;
[0150] The inorganic electrolyte salt is LiBF4;
[0151] The second type of solid electrolyte particles is Li2S-P2S5-LiCl;
[0152] The particle size D50 parameter of Li2S-P2S5-LiCl particles is 0.4±0.2um;
[0153] The particle size D50 parameter of the second type of composite solid electrolyte particles 114 is 0.6±0.15 um;
[0154] The surface coating thickness of the third type of composite solid electrolyte is 5 to 20 nm;
[0155] The ratio of Li2S-P2S5-LiCl to the third type of composite solid electrolyte particles 115 is 60:40;
[0156] Step 6: preparing an active material coating 110,
[0157] The composite active material particles, composite solid electrolyte particles, conductive agent, and adhesive are uniformly mixed according to a certain ratio, and then the adhesive is fiberized and granulated so that the adhesive fibers fully contact and cover the composite active material particles and the composite solid electrolyte particles; the composite active material particles, composite solid electrolyte particles, and conductive agent covering the adhesive fibers are formed into an active material coating 110 by a press film forming device;
[0158] The adhesive is PTFE;
[0159] The thickness of the active material coating 110 is 200 um;
[0160] The ratio of the composite active material particles in the above step 2 / step 3, the composite solid electrolyte particles in the above step 1 / step 4 / step 5, the conductive agent, and the adhesive is 80:15:2:3;
[0161] The weight ratio of the first type of composite solid electrolyte particles 113, the second type of composite solid electrolyte particles 114 and the third type of composite solid electrolyte particles 115 is 50:35:15;
[0162] Step 7: preparing a high-performance all-solid-state battery electrode 100.
[0163] The current collector 120 and the active material coating 110 are pressed into a low-porosity, high-performance all-solid-state battery pole piece 100 under certain temperature and pressure conditions using a multi-roll hot pressing device;
[0164] The temperature of the first section of the multi-roll hot pressing equipment is 50°C, the temperature of the second section is 80°C, and the temperature of the third section is 15°C;
[0165] The pressure of the first section of the multi-roll hot pressing equipment is 10MPa, the pressure of the second section is 35MPa, and the pressure of the third section is 80MPa;
[0166] Step 8, using the above-mentioned all-solid-state positive electrode sheet and all-solid-state negative electrode sheet and an externally purchased all-solid-state electrolyte membrane to form a 2Ah all-solid-state battery;
[0167] Step 9, the solid-state battery is subjected to 50% SOC-DCR, rate (1C), and 0.5C-100% DOD cycle tests. The results are shown in Table 1.
[0168] Embodiment 2:
[0169] The difference from Example 1 is that the organic polymer solid electrolyte used in this example is PMMA, and the rest is the same as Example 1.
[0170] Embodiment 3:
[0171] The difference from Example 1 is that the inorganic electrolyte salt used in the third type of composite solid electrolyte in this example is LiPF6, and the rest is the same as Example 1.
[0172] Embodiment 4:
[0173] Different from Example 1, the inorganic electrolyte salt used in this example is NaBF4, and the corresponding active material is NaNi3Fe3Mn3Cu1O2, and the rest is the same as Example 1.
[0174] Embodiment 5:
[0175] Different from Example 1, the active material used in this example is hard carbon, the battery electrode is made of negative electrode, and the rest is the same as Example 1.
[0176] Embodiment 6:
[0177] Different from Example 1, the weight ratio of the third type of composite solid electrolyte particles 115 to the inorganic electrolyte salt in this embodiment is 95:5; the rest is the same as Example 1.
[0178] Embodiment 7:
[0179] Different from Example 1, in this embodiment, the particle size D50 parameter of the third type of composite solid electrolyte particles 115 is 0.25±0.05 um; the rest is the same as Example 1.
[0180] Embodiment 8:
[0181] Different from Example 1, in this embodiment, the particle size D50 parameter of the first type of active material particles 1111 is 3.3±0.2 um; the D50 parameter of the first type of composite active material particles 111 is 3.7±0.15 um; the rest is the same as Example 1.
[0182] Embodiment 9:
[0183] Different from Example 1, in this embodiment, the ratio of the first type of active material particles 1111 to the third type of composite solid electrolyte particles 115 is 95:5; the rest is the same as Example 1.
[0184] Embodiment 10:
[0185] Different from Example 1, in this embodiment, the particle size D50 parameter of the second type active material particles 1121 is 1.8±0.2 um; the particle size D50 parameter of the second type composite active material particles 112 is 2.4±0.15 um; the rest is the same as Example 1.
[0186] Embodiment 11:
[0187] Different from Example 1, in this embodiment, the ratio of the second type active material particles 1121 to the third type composite solid electrolyte particles 115 is 90:10; the rest is the same as Example 1.
[0188] Embodiment 12:
[0189] Different from Example 1, in this embodiment, the particle size D50 parameter of the first type of inorganic solid electrolyte particles 1131 is 1.5±0.2um; the D50 parameter of the first type of composite solid electrolyte particles 113 is 2.0±0.15um; the rest is the same as Example 1.
[0190] Embodiment 13:
[0191] Different from Example 1, in this embodiment, the ratio of the first type of inorganic solid electrolyte particles 1131 to the third type of composite solid electrolyte particles 115 is 90:10; the rest is the same as Example 1.
[0192] Embodiment 14:
[0193] Different from Example 1, in this embodiment, the particle size D50 parameter of the second type of inorganic solid electrolyte particles 1141 is 0.6±0.2um; the D50 parameter of the second type of composite solid electrolyte particles 114 is 0.8±0.15um; the rest is the same as Example 1.
[0194] Embodiment 15:
[0195] Different from Example 1, in this embodiment, the ratio of the second type of inorganic solid electrolyte particles 1141 to the third type of composite solid electrolyte particles 115 is 80:20; the rest is the same as Example 1.
[0196] Embodiment 16:
[0197] Different from Example 1, the ratio of the composite active material particles, the composite solid electrolyte particles, the conductive agent, and the adhesive in this example is 90:8:1:1; the rest is the same as Example 1.
[0198] Embodiment 17:
[0199] Different from Example 1, in this embodiment, the weight ratio of the first type of composite solid electrolyte particles 113, the second type of composite solid electrolyte particles 114 and the third type of composite solid electrolyte particles 115 is 70:25:5; the rest is the same as Example 1.
[0200] Comparative Example 1:
[0201] Different from Example 1, the active material and the inorganic solid electrolyte in this comparative example are not coated with the third type of composite solid electrolyte, and other proportions and processes are the same as those in Example 1.
[0202] Comparative Example 2:
[0203] Different from Example 1, the active substances in this comparative example are not divided into the first type of active substances and the second type of active substances, and other proportions and processes are the same as those in Example 1.
[0204] Comparative Example 3:
[0205] Different from Example 1, the inorganic solid electrolyte in this comparative example is not divided into the first type of inorganic solid electrolyte and the second type of inorganic solid electrolyte, and other proportions and processes are the same as those in Example 1.
[0206] Comparative Example 4:
[0207] Different from Example 1, the weight ratio of the third type of composite solid electrolyte particles 115 to the inorganic electrolyte salt in this comparative example is 75:25; the rest is the same as Example 1.
[0208] Comparative Example 5:
[0209] The difference from Example 1 is that the particle size D50 parameter of the third type of composite solid electrolyte particles 115 in this comparative example is 0.55±0.05 um; the rest is the same as Example 1.
[0210] Comparative Example 6:
[0211] Different from Example 1, in this comparative example, the ratio of the first type of composite active material particles 111 to the second type of composite active material particles 112 is 90:10; the rest is the same as Example 1.
[0212] Comparative Example 7:
[0213] Different from Example 1, in this comparative example, the ratio of the first type of active material particles 1111 to the third type of composite solid electrolyte particles 115 is 80:20; the rest is the same as Example 1.
[0214] Comparative Example 8:
[0215] Different from Example 1, in this comparative example, the particle size D50 parameter of the first type of composite active material particles 111 is 5.0 um, and the particle size D50 parameter of the first type of active material particles 1111 is 4.5 um; the rest is the same as Example 1.
[0216] Comparative Example 9:
[0217] Different from Example 1, in this comparative example, the ratio of the second type active material particles 1121 to the third type composite solid electrolyte particles 115 is 70:30; the rest is the same as Example 1.
[0218] Comparative Example 10:
[0219] Different from Example 1, in this comparative example, the particle size D50 parameter of the second type composite active material particles 112 is 1.0 um, and the particle size D50 parameter of the second type active material particles 1121 is 0.6 um; the rest is the same as Example 1.
[0220] Comparative Example 11:
[0221] Different from Example 1, in this comparative example, the ratio of the first type of inorganic solid electrolyte particles 1131 to the third type of composite solid electrolyte particles 115 is 65:35; the rest is the same as Example 1.
[0222] Comparative Example 12:
[0223] Different from Example 1, in this comparative example, the particle size D50 parameter of the first type of solid electrolyte particles is 3.0 um, and the particle size D50 parameter of the first type of inorganic solid electrolyte particles 1131 is 2.5 um; the rest is the same as Example 1.
[0224] Comparative Example 13:
[0225] Different from Example 1, in this comparative example, the ratio of the second type of inorganic solid electrolyte particles 1141 to the third type of composite solid electrolyte particles 115 is 50:50; the rest is the same as Example 1.
[0226] Comparative Example 14:
[0227] Different from Example 1, in this comparative example, the particle size D50 parameter of the second type of composite solid electrolyte particles 114 is 0.3 um, and the particle size D50 parameter of the second type of inorganic solid electrolyte particles 1141 is 0.1 um; the rest is the same as Example 1.
[0228]
[0229]
[0230]
[0231] Table 1 Test data of each group of embodiments and comparative examples
[0232] It can be seen from the results in Table 1 that the solid-state battery made using the low-porosity and low-impedance all-solid-state battery electrode 100 provided by the present invention has a lower DC resistance in the battery charging state, and the battery rate and cycle capacity retention rate are significantly improved.
[0233] The above description is only a preferred embodiment of the present invention, and does not limit the implementation mode and protection scope of the present invention. For those skilled in the art, it should be aware that all solutions obtained by equivalent substitutions and obvious changes made using the description and illustrations of the present invention should be included in the protection scope of the present invention.
Claims
1. A high-performance all-solid-state battery electrode, comprising a current collector and an active material coating disposed on the surface of the current collector, characterized in that: The active material coating includes uniformly mixed composite active material particles, composite solid electrolyte particles, a conductive agent and a binder; the composite active material particles include first-type composite active material particles whose surfaces are coated with third-type composite solid electrolyte particles and second-type composite active material particles whose surfaces are coated with the third-type composite solid electrolyte particles; the composite solid electrolyte particles include first-type composite solid electrolyte particles whose surfaces are coated with the third-type composite solid electrolyte particles, second-type composite solid electrolyte particles whose surfaces are coated with the third-type composite solid electrolyte particles, and the third-type composite solid electrolyte particles.
2. The all-solid-state battery pole piece according to claim 1, characterized in that: The current collector is a positive electrode current collector or a negative electrode current collector, and the positive electrode current collector is one of aluminum foil, microporous aluminum foil, corroded aluminum foil, composite aluminum foil, copper foil, microporous copper foil, corroded copper foil, composite copper foil, steel foil, corroded steel foil and microporous steel foil; the negative electrode current collector is one of aluminum foil, microporous aluminum foil, corroded aluminum foil, composite aluminum foil, copper foil, microporous copper foil, corroded copper foil, composite copper foil, steel foil, corroded steel foil and microporous steel foil; The thickness of the positive electrode current collector is 4 um to 20 um, and the thickness of the negative electrode current collector is 4 um to 15 um.
3. The all-solid-state battery pole piece according to claim 1, characterized in that: The first type of composite active material particles include first type of active material particles and third type of composite solid electrolyte particles coated on the surface of the first type of active material particles, and the coating thickness is 30nm to 100nm; The ratio of the first type of active material particles to the third type of composite solid electrolyte particles is (90:10) to (95:5); The particle size D50 parameter of the first type of composite active material particles is 3.0 um to 4.0 um, and the particle size D50 parameter of the first type of active material particles is 2.5 um to 3.5 um.
4. The all-solid-state battery pole piece according to claim 1, characterized in that: The second type of composite active material particles include the second type of active material particles and the third type of composite solid electrolyte particles coated on the surface of the second type of active material particles, and the coating thickness is 10nm to 50nm; The ratio of the second type of active material particles to the third type of composite solid electrolyte particles is (80:20) to (90:10); The particle size D50 parameter of the second type of composite active material particles is 1.5um to 2.5um, and the particle size D50 parameter of the second type of active material particles is 0.8um to 1.8um.
5. The all-solid-state battery pole piece according to claim 1, characterized in that: The ratio of the first type of composite active material particles to the second type of composite active material particles contained in the composite active material particles is (55:45) to (80:20); The weight ratio of the first type of composite solid electrolyte particles, the second type of composite solid electrolyte particles and the third type of composite solid electrolyte particles included in the composite solid electrolyte particles is (50:35:15) to (70:25:5).
6. The all-solid-state battery pole piece according to claim 1, characterized in that: The first type of composite solid electrolyte particles include first type of inorganic solid electrolyte particles and the third type of composite solid electrolyte particles coated on the first type of inorganic solid electrolyte particles, with a coating thickness of 10nm to 50nm; The ratio of the first type of inorganic solid electrolyte particles to the third type of composite solid electrolyte particles is (75:25) to (90:10); The particle size D50 parameter of the first type of composite solid electrolyte particles is 1.2um to 2.0um, and the particle size D50 parameter of the first type of inorganic solid electrolyte particles is 0.8um to 1.5um; The first type of inorganic solid electrolyte particles is an inorganic oxide solid electrolyte or a sulfide solid electrolyte or a mixture of an inorganic oxide solid electrolyte and a sulfide solid electrolyte.
7. The all-solid-state battery pole piece according to claim 1, characterized in that: The second type of composite solid electrolyte particles include second type of inorganic solid electrolyte particles and the third type of composite solid electrolyte particles coated on the surface of the second type of inorganic solid electrolyte particles, and the coating thickness is 5nm to 30nm; The ratio of the second type of inorganic solid electrolyte particles to the third type of composite solid electrolyte particles is (60:40) to (80:20); The particle size D50 parameter of the second type of composite solid electrolyte particles is 0.4um to 0.8um, and the particle size D50 parameter of the second type of inorganic solid electrolyte particles is 0.2um to 0.6um; The second type of inorganic solid electrolyte particles is an inorganic oxide solid electrolyte or a sulfide solid electrolyte or a mixture of an inorganic oxide solid electrolyte and a sulfide solid electrolyte.
8. The all-solid-state battery pole piece according to claim 1, characterized in that: The active material coating is a positive electrode active material coating or a negative electrode active material coating, the thickness of the positive electrode active material coating is 10um to 300um, and the thickness of the negative electrode active material coating is 10um to 300um; The composite active material particles are positive electrode composite active material particles or negative electrode composite active material particles, and the conductive agent is a positive electrode conductive agent or a negative electrode conductive agent; the positive electrode active material coating includes the positive electrode composite active material particles, the positive electrode conductive agent, the composite solid electrolyte particles and the adhesive; the negative electrode active material coating includes the negative electrode composite active material particles, the negative electrode conductive agent, the composite solid electrolyte particles and the adhesive.
9. The all-solid-state battery pole piece according to claim 8, characterized in that: The positive active material of the positive composite active material particles includes LiCoO2, LiNi x Co y Mn z O2(x+y+z=1), LiNi x Co y Al z O2(x+y+z=1),NaNi x Fe y Mn z Cu w O2(x+y+z+w=1), Na x At least one of M1[M2(CN)6](0<x<6); The positive electrode active material of the negative electrode composite active material particles includes graphite, Si, Li4Ti5O 12 , at least one of hard carbon and soft carbon; The positive electrode conductive agent includes at least one of electric carbon black, carbon nanotubes, graphene and carbon fibers, and the negative electrode conductive agent includes at least one of electric carbon black, carbon nanotubes, graphene and carbon fibers.
10. The all-solid-state battery pole piece according to claim 1, characterized in that: The third type of composite solid electrolyte particles is a mixture of an organic polymer solid electrolyte and an inorganic electrolyte salt, with a weight ratio of (85:15) to (95:5); wherein the organic polymer solid electrolyte is at least one of polyethylene oxide, polymethyl methacrylate, polyvinylidene fluoride-copolymer, and hydrogenated nitrile rubber, and the inorganic electrolyte salt is at least one of lithium hexafluorophosphate, sodium hexafluorophosphate, lithium tetrafluoroborate, sodium tetrafluoroborate, sodium bis(trifluoromethylsulfonyl)imide, lithium bis(trifluoromethylsulfonyl)imide, lithium difluoroborate, and sodium difluoroborate; The particle size D50 parameter of the third type of composite solid electrolyte particles is 0.1um to 0.3um.
11. A method for preparing a high-performance all-solid-state battery electrode, characterized in that: For preparing the all-solid-state battery pole piece as claimed in any one of claims 1 to 10, comprising: Step S1, fully melting the organic polymer solid electrolyte under a certain temperature and stirring conditions, adding an inorganic electrolyte salt, and fully mixing them under a certain temperature and stirring conditions to form a molten slurry; Step S2, spraying and cooling the molten slurry to obtain the third type of composite solid electrolyte particles; adding the first type of active material particles to the molten slurry and mixing them thoroughly, spraying and cooling to obtain the first type of composite active material particles; adding the second type of active material particles to the molten slurry and mixing them thoroughly, spraying and cooling to obtain the second type of composite active material particles; adding the first type of inorganic solid electrolyte particles to the molten slurry and mixing them thoroughly, spraying and cooling to obtain the first type of composite solid electrolyte particles; adding the second type of inorganic solid electrolyte particles to the molten slurry and mixing them thoroughly, spraying and cooling to obtain the second type of composite solid electrolyte particles; Step S3, uniformly mixing the composite active material particles, the composite solid electrolyte particles, the conductive agent, and the adhesive according to a certain ratio, processing the adhesive into adhesive fibers, and making the composite active material particles, the composite solid electrolyte particles, and the conductive agent coated with the adhesive fibers into the active material coating; Step S4, pressing the current collector and the active material coating by multi-roll hot pressing under certain temperature and pressure conditions to obtain the all-solid-state battery electrode.
12. The method for preparing an all-solid-state battery pole piece according to claim 11, characterized in that: In step S3, the adhesive includes at least one of polyvinylidene fluoride, polytetrafluoroethylene, polyvinyl alcohol, and polyacrylic acid, the thickness of the active material coating is 50um to 300um, and the ratio of the composite active material particles, the composite solid electrolyte particles, the conductive agent, and the adhesive is (80:15:2:3) to (90:8:1:1); In step S4, the temperature of the first section of the multi-roller hot pressing is 45°C to 60°C, the temperature of the second section is 80°C to 100°C, the temperature of the third section is 15°C to 30°C, the pressure of the first section is 5MPa to 20MPa, the pressure of the second section is 30MPa to 60MPa, and the pressure of the third section is 70MPa to 100MPa.